Doubly charged Higgs from e-gamma scattering in the 3-3-1 Model - Cieza Montalvo, J. E.; Ramirez Ulloa, G. H.; Tonasse, M. D. [UNESP] (Springer, 2012)
We studied the production and signatures of doubly charged Higgs bosons in the process gamma e(-) -> H--E+, where E+ is a heavy lepton, at the e(-)e(+) International Linear Collider (ILC) and CERN Linear Collider (CLIC). The intermediate photons are given by the Weizsacker-Williams and laser-backscattering distributions. We found that significant signatures are obtained by bremsstrahlung and backward Compton scattering of laser. A clear signal can be obtained for doubly charged Higgs bosons, doubly charged gauge bosons and heavy leptons.